The Effectiveness of Using E-Flashcard Based Web Media on Student's Vocabulary Mastery at SMPN 1 Laren - Nur Aang Citra Agustin; M Labib Al Halim (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2026)
This study aims to determine the effect of using e-flashcards on vocabulary mastery. The type of research conducted by this researcher is quantitative research with a pre-experimental design. The research participants in this study consisted of Class VIII students at SMP N 1 Laren in the 2024/2025 academic year. A total of 24 students were selected as participants. The technique used by researchers in collecting data was a test (pretest and posttest). In analyzing the data, researchers used quantitative data analysis by comparing the results of the pre-test and posttest. The results of the study showed that there was a significant difference in the use of e-flashcards to improve students' vocabulary mastery. This is evidenced by the increase in the average pretest score of 53.83 to 85.17 in the average posttest score. In addition, based on the results of the t-test, it can be seen that sig (2-tailed) 0.000 is smaller than 0.05. This means that after implementing the e-flashcard strategy, it has a significant effect on English vocabulary mastery.